Penggunaan Youtuber sebagai Konten Edukasi Pariwisata Korea Selatan Selama Pandemi oleh KTO Jakarta - Leonita Kusumawardhani (Departement of Mathematics Education, 2023)
South Korea is one of the countries that has become a foreign tourism destination for the people of Indonesia. Every year the Korean Tourism Organization (KTO) Jakarta records an increase in the number of visits to the country of ginseng. This figure dropped dramatically during the Covid -19 pandemic, due to travel bans from the Indonesian people and also the closure of the border. However, KTO Jakarta continues to carry out promotions using several Youtubers to introduce tourism destinations in South Korea. The Youtubers invited to collaborate are Indonesian Youtubers who are currently domiciled in South Korea and South Korean Youtubers who have lived in Indonesia, who use the Indonesian language in their content. The research method used in this study is qualitative content analysis of Youtuber content, Jang Hansol and Kimbab Family, which are the unit of analysis in this study. The results of this study indicate that in order to create effective tourism content, in addition to attractive and aesthetic visuals, accuracy must also be considered, transparency (complete, relevant, and meaningful for the audience), and credibility (credibility and trust). From the results of this study, it can be seen that KTO Jakarta has selected the right Youtuber according to the audience they want. This research is expected to contribute to educational content for tourism destinations for content creators and also the Government to promote Indonesian tourism destinations.